Minocycline attenuates lipopolysaccharide (LPS)-induced neuroinflammation, sickness behavior, and anhedonia - Bailey Michael T; Himler Justin; Hanke Mark; Wynne Angela; Huang Yan; Henry Christopher J; Sheridan John F; Godbout Jonathan P (Journal of Neuroinflammation, 2008)
Abstract Background Activation of the peripheral innate immune system stimulates the secretion of CNS cytokines that modulate the behavioral symptoms of sickness. Excessive production of cytokines by microglia, however, may cause long-lasting behavioral and cognitive complications. The purpose of this study was to determine if minocycline, an anti-inflammatory agent and purported microglial inhibitor, attenuates lipopolysaccharide (LPS)-induced neuroinflammation, sickness behavior, and anhedonia. Methods In the first set of experiments the effect of minocycline pretreatment on LPS-induced microglia activation was assessed in BV-2 microglia cell cultures. In the second study, adult (3–6 m) BALB/c mice received an intraperitoneal (i.p.) injection of vehicle or minocycline (50 mg/kg) for three consecutive days. On the third day, mice were also injected (i.p.) with saline or Escherichia coli LPS (0.33 mg/kg) and behavior (i.e., sickness and anhedonia) and markers of neuroinflammation (i.e., microglia activation and inflammatory cytokines) were determined. In the final study, adult and aged BALB/c mice were treated with the same minocycline and LPS injection regimen and markers of neuroinflammation were determined. All data were analyzed using Statistical Analysis Systems General Linear Model procedures and were subjected to one-, two-, or three-way ANOVA to determine significant main effects and interactions. Results Minocycline blocked LPS-stimulated inflammatory cytokine secretion in the BV-2 microglia-derived cell line and reduced LPS-induced Toll-like-receptor-2 (TLR2) surface expression on brain microglia. Moreover, minocycline facilitated the recovery from sickness behavior (i.e., anorexia, weight loss, and social withdrawal) and prevented anhedonia in adult mice challenged with LPS. Furthermore, the minocycline associated recovery from LPS-induced sickness behavior was paralleled by reduced mRNA levels of Interleukin (IL)-1β, IL-6, and indoleamine 2, 3 dioxygenase (IDO) in the cortex and hippocampus. Finally, in aged mice, where exaggerated neuroinflammation was elicited by LPS, minocycline pretreatment was still effective in markedly reducing mRNA levels of IL-1β, TLR2 and IDO in the hippocampus. Conclusion These data indicate that minocycline mitigates neuroinflammation in the adult and aged brain and modulates the cytokine-associated changes in motivation and behavior.